Accuracy of liquid‐based cytology (LBC) in the oral mucosa according to novel diagnostic guidelines in Japan: Classification of cytology for oral mucosal disease (JSCC, 2015). Issue 1 (8th October 2019) - Kondo, Yuko; Oya, Kaori; Sakai, Manabu; Fujiwara, Chisato; Tojo, Fumiaki; Usami, Yu; Fukuda, Yasuo; Kogo, Mikihiko; Kishino, Mitsunobu
Abstract: Introduction: Recently, the applications of liquid‐based cytology (LBC) have been extended to oral cytology, and in 2015, diagnostic guidelines having roots in the Bethesda System for oral exfoliative cytology were published by the Japanese Society of Clinical Cytology (JSCC): Classification of cytology for oral mucosal disease (JSCC, 2015). Here we aimed to evaluate the applicability of LBC in the oral mucosa in accordance with the novel diagnostic guidelines. Methods: Two preparation techniques (conventional exfoliative cytology [CEC] with LBC and LBC alone) were used in this study. Intraepithelial lesions of the oral mucosa histologically diagnosed by biopsy or resection materials were selected as samples and multiple intraepithelial lesions in a single patient were counted. Deep‐seated lesions under the oral mucosa were excluded. The performance of cytological diagnosis was evaluated in each technique by comparing cytological diagnoses with histological diagnoses in accordance with the diagnostic guidelines. Results: The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of cytological diagnosis in CEC with LBC were 61%, 73%, 86%, 41%, and 64% ( P ≤ .023), respectively. For LBC alone, these values were 55%, 79%, 92%, 29%, and 60% ( P ≤ .024), respectively. The rates of inadequate samples were 0.83% for CEC with LBC and 1.2% for LBC alone against whole samples. Conclusion: LBC showed good specificity, positive predictive value, and low rate of inadequate specimen, so it was suitable for oral cytology. The data used for this study reflect a large contribution in daily medical examination.